Motivasi Masyarakat Menjadi Pengojek Becak Motor di Kenagarian Barung-Barung Belantai Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan. - Verlina, Mutia; Erita, Yeni; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This study aimed to obtain data and information are : 1) the level of income. 2) the level of knowledge. 3) previouns livelihoods. 4) culture condisions. 5) lack of transportation infarstructure. This type of research is descriptive, which became the overall study population were people who became motor tricycles di kenagarian Barung sub-Barung Belantai Koto XI Tarusan southern coastal distric, which consists of several villages : Pasa Ambacang, Lubuak Buayo, Koto Kaciak, Pasa, Palo Pasa, Kalan land, hills, terrain, Parik and Rajo Agam. The Â samples were taken in total sampling number thatÂ  is equal to 51 motorcycle ricksaw. The result of this study indicate : 1) income motorcyle rickshaw, it can be seen that their avarage income is around Rp. > 500.000 â 1.000.000 2) Knowledge is not a motivation to motorcycle rickshaw, but they generally have is this knowledge it can be seen that they knew with light traffic sign in every custumerÂ  asks about a region or place they want to go general they know, but based on interview, avarege their averege graduated from elementary school and junior high school, so that those who answer the many lack of the skill and skill. 3) provious livelihood society motor tricycle rickshaw, it can be seen that their live mediocre after being motorcycle rickshaw, sometimes they look for another job to make end meet. 4) the community of motor tricycle are not shy with their profession that can be seen in general society who are not ashamed to answer as many as 44 people (86,27%). 5) that the motivation motorcycle rickshaw society are the lack of transport infrastructure, it can be seen that a society that say yes 45 people (88,23%) of the 51 respondents who answered.